Assessing stress conditions and impact velocities in fluidized bed opposed jet mills - Strobel, Alexander; Köninger, Benedikt; Romeis, Stefan; Schott, Florian; Wirth, Karl Ernst; Peukert, Wolfgang (Particuology, 2020)
Fluidized bed opposed jet mills are capable of meeting the continuously growing demand for contamination-free fine particles. In this type of jet mill, the solid material is entrained and accelerated by expanding gas jets that are focused onto a focal point inside a fluidized bed. The resulting particle collisions induce breakage. The process is affected by the relative particle velocities and the number of particle–particle collisions. Clearly, both quantities are distributed. However, to date, neither relative particle velocities nor collision frequencies in such units have been determined. The present work introduces an innovative method to assess the stressing conditions in jet mills experimentally. To this end, mixtures of glass and ductile metal microspheres were used, with the latter employed in small amounts. Inter-particle collisions between the aluminum and glass spheres lead to the formation of dents on the microparticles. The size and number of these dents are associated with the individual collision velocities and overall collision frequencies. The correlation between dent size and collision velocity was obtained from finite element calculations based on empirical data. The proposed approach was validated using particle image velocimetry during secondary gas injection into a fluidized bed reactor. In this case the effect of the distance between two opposed nozzles was examined. For a lab-scaled fluidized bed opposed jet mill the effects of gas pressure and hold-up were investigated. Relative particle velocities were found to be significantly lower than the gas velocities, while the number of contacts per particle was determined to be extremely high.
CRIS-Team Scopus Importer:2020-07-03
Keywords: Finite element modeling; Fluidized bed opposed jet mill; Relative velocity distribution; Single particle probes; Stress number distribution

Assessing the influence of viscosity and milling bead size on the stressing conditions in a stirred media mill by single particle probes - Strobel, Alexander; Schwenger, Jan; Wittpahl, Sandra; Schmidt, Jochen; Romeis, Stefan; Peukert, Wolfgang (Chemical Engineering Research & Design, 2018)
Keywords: Fluid viscosity; Grinding media size; Stress number and energy distribution; Single particle probes; Stirred media milling

Characterization of stressing conditions in mills – A comprehensive research strategy based on well-characterized model particles - Strobel, Alexander; Romeis, Stefan; Wittpahl, Sandra; Herre, Patrick; Schmidt, Jochen; Peukert, Wolfgang (Powder Technology, 2017)
Despite the abundant industrial use of various wet mills a detailed understanding of the mechanisms involved is far from being complete. During comminution stress distributions are applied to the individual particles of a processed suspension. In fact, the type of stressing and the acting stress energies are distributed. The distributions of acting stress energy and number of stress events per product particle are governed by the used mill and its operational conditions. Mill functions link the stress energy and stress number distributions to the operating parameters and are so far unknown. We introduce a new methodology to directly characterize the effective stress energy and effective stress number distributions within stirred media mills: Mechanically fully characterized spherical particles are used as particulate probes. The underlying finite element model for the energetic behavior of the probes during uniaxial compression is supported by manipulation experiments on the single particle level. The deformation behavior of individual particles and the respective changes of the particles’ shapes are used to determine the stressing history of the particles and hence the stress energy and stress number distributions in the mill. Experimental limitations and prospects of the proposed methodology are outlined in detail. The new approach is comprehensively discussed for a lab-scale stirred media mill operated at exemplary process conditions. The transfer to other mills or unit operations, however, is straightforward.
Keywords: Finite element modelling; Single particle compression; Single particle probes; Stress energy distribution; Stress number distribution

Impact comminution in jet mills - Strobel, Alexander; Köninger, Benedikt; Romeis, Stefan; Wirth, Karl Ernst; Peukert, Wolfgang (Dynamic Flowsheet Simulation of Solids Processes, 2020)
Modelling the comminution in jet mills with respect to the complex twophase flow and the dynamic process behaviour is still a challenging task. The processed solids pass through several stages in the mill: The comminution process in the lower part, the pneumatic transport towards the classifier in the middle section, and the classification step at the top. In this contribution, the grinding kinetics and process behaviour during quasi-batch and fed-batch operational mode for different holdups, classifier speeds, and particle sizes are examined in detail. A previously developed method using well-characterized aluminium particle probes to access the stressing conditions is adapted for application in the investigated jet mill: The relative particle impact velocity is linked to the geometric changes of the particles upon impact. A high number of impact events happen in the mill, while at the same time, the average particle velocity is comparatively low. Besides the stressing conditions, breakage probabilities for the used glass beads are determined by single particle impact experiments and described by the model of Vogel and Peukert. Solids concentration measurements and high-speed imaging reveal the formation of particle clusters at the classifier and its periphery. These clusters have a massive impact on the classification step itself: Fine particles are trapped inside the clusters and are not discharged. Based on an adaption of the breakage model, and using the mean relative particle impact velocity determined by the particle probes, a model for the product mass flow is introduced.
CRIS-Team Scopus Importer:2020-08-28

Prallzerkleinerung in Fließbettgegenstrahlmühlen: Vom Einzelkorn zur Mühle - Romeis, Stefan; Köninger, Benedikt; Strobel, Alexander; Wirth, Karl-Ernst; Peukert, Wolfgang (Chemie Ingenieur Technik, 2016)
Keywords: zerkleinerung; prallmühle; partikel

Scalable production of glass flakes via compression in the liquid phase - Esper, Julian Duane; Liu, Lingfeng; Willnauer, Johannes; Strobel, Alexander; Schwenger, Jan; Romeis, Stefan; Peukert, Wolfgang (Advanced Powder Technology, 2020)
A comprehensive study on controlled shape formation with high yield of three commercially relevant SiO2-based amorphous glasses in a stirred media mill is presented. Stressing under well-controlled conditions leads to micron-sized amorphous glass flakes with high aspect ratios. This unique result is quite contrary to the fundamental observation that comminution processes generally result in irregular shaped particles. The influences of glass composition, processing time, stirrer tip speed and grinding media size on the obtained products have been investigated. The size and shape of the obtained glass flakes have been characterized by scanning electron microscopy and atomic force microscopy. The glass flakes exhibit thicknesses as low as 155 nm while the lateral dimensions are well within the micrometer range. Our study shows that particle size reduction occurs within the first hour of grinding. Afterwards plastic deformation of the fragments, which can be accompanied by densification of the glass network, leads to the formation and further thinning of the glass flakes. To demonstrate the quality and applicability of the glass flakes interference pigments were realized by a TiO2 coating via an aqueous titration process. The presented approach offers a simple, convenient and fully scalable top-down method to produce flake-like particles from various silica glasses. The obtained flakes are suitable substrates for further modifications and applications and the process can be transferred to other materials and glasses with tailor-made chemical composition
Keywords: Stirred media mill; Comminution; Liquid phase compression; Particle processing; Glass flakes; Pigments